World of Life, Habitus, and Reproduction in the Analysis of Social Segmentation of Chilean Education - Sánchez Oñate, Alejandro (2019)
This paper provides a conceptual review of the contributions of sociology in understanding the social segmentation of education, particularly from the case of the Chilean education system. Here, with the lifeworld of social phenomenology provided by Alfred Schutz and the concepts of habitus and reproduction incorporated by Pierre Bourdieu, empirical data regarding the Chilean educational context showing expressions of segmentation and other forms of inequality in school and university education are reviewed.